Azerbaijan : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1998)
This paper describes economic developments in the Azerbaijan Republic during the 1990s. Real GDP declined by more than 70 percent from 1992 to 1995, by which time high inflation had eroded real incomes, the exchange rate had weakened, and international reserves were nearly depleted. In early 1995, the authorities started a comprehensive stabilization program supported by the IMF's Structural Transformation Facility. Fiscal and credit policies were tightened, while a number of structural reforms were introduced, mainly in the areas of exchange and trade liberalization.